Cryoballoon ablation for paroxysmal atrial fibrillation in septuagenarians: a prospective study - Chierchia GB; Capulzini L; de Asmundis C; Sarkozy A; Sorgente A; Yazaki Y; Muller Burri SA; Paparella G; Lamier M; Bayrak F; Brugada P.; DE PONTI, ROBERTO (2010)
Aims: To evaluate the effects of pulmonary vein isolation (PVI) in terms of feasibility, safety and success rate on a midterm follow-up period in septuagenarians undergoing ablation with the Arctic Front Cryoballoon for atrial fibrillation (AF). Methods and Results: We prospectively enrolled 21 patients aged 70 years or older (14 male; age 73 ± 2.5 years) elected to circumferential PVI with the 28mm cryoballoon for symptomatic drug resistant paroxysmal AF. A total number of 82 pulmonary veins (PV) were evidenced. Successful isolation could be obtained in all 82 (100%) PV ostia at the end of procedure. No major complication occurred during procedure. At a mean follow-up of 11.5 ± 4.7 months following ablation, 62% of patients did not present recurrence of atrial arrhythmias. Conclusion: Cryoballoon ablation may be feasible and safe in older patients. Moreover a large proportion of the latter did not present AF recurrence during follow-up.